PREVALENCE AND INTENSITY OF NEMATODE PARASITES OF Poecilia reticulata PETERS (1859) IN FOUR WASTEWATER DRAINS OF LAGOS STATE, NIGERIA (2013)
Poecilia reticulata (guppy) a common ornamental tropical fish is found in many wastewater drains in Nigeria. Guppies feed on copepods which are intermediate hosts of some nematode parasites of culturable fish species. The restriction on the importation of ornamental fishes into Nigeria has enhanced the demand for local species, usually sourced from the wild. There is dearth of information on the parasites of ornamental fishes in Nigeria. This study was aimed at determining prevalence and mean intensity of the nematode parasites of P. reticulata from four waste water drains in Lagos State.